Показники систем коагуляції та фібринолізу, маркери запалення у хворих на цукровий діабет 2-го типу з ожирінням - Кехіопуло, Х. Ф. (Clinical Endocrinology and Endocrine Surgery, 2013)
The author presents the data on a study of the markers of inflammation levels and state of the coagulation and fibrinolytic system components systems in patients with type 2 diabetes mellitus (DM) and visceral obesity in connection with cardiovascular diseases risk factors. With this purpose, 56 patients have been followed up. The control group included 20 patients corresponding on age and durations of type 2 DM but without abdominal obesity. It has been shown that procoagulant changes are marked at absolute majority of type 2 DM patients with visceral obesity (94.6%), in 64.3% patients these changes were connected with the defeat of a few links of the coagulation blood system. The most frequent changes of hemostasis is an increase of activity of plasminogen activator inhibitor 1 (87.5%), that represents insufficiency of fibrinolysis; increase of activity of coagulation factor VIII (53.6%) and testifies to activating of external cascade of hemopexis, and insufficiency of the anticoagulating system of protein C (23.2%). Chronic subacute system inflammation in type 2 DM patients with visceral obesity shows up the reliable increase of concentration of markers of inflammation – fibrinogen and Ñ-reactive protein, and also by the decline of adiponectin level. Expressed of proinflammatory and procoagulanting changes in patients with type 2 DM and visceral obesity associated with the anthropometric and biochemical markers of obesity.